TRANSNATIONAL PROJECTS IN HIGHER EDUCATION: DEVELOPMENT OF INTERCULTURAL COMMUNICATION SKILLS BY MEANS OF JOINT RESEARCH - Gradaleva, Ekaterina; Houston, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article analyses the efficiency of implementing transnational virtual projects in higher education. The research aims at defining the most appropriate ways of developing intercultural communication skills among students in the process of doing joint research. The authors describe the International Conference Project on Global Issues held at Samara State Technical University (Russia) and Notre Dame College (USA). Special emphasis is laid upon the stages of the project programme worked out by the authors, difficulties in communication faced by students in the course of collaboration and the ways to eliminate them. The authors assess project efficiency not only by analysing psychological and cultural factors, but also by examining the data of the questionnaire survey held among Russian and American students who have finished their joint research. This kind of multifaceted approach helped identify advantages and disadvantages of the project programme and reveal the friction points that can arise in the process of professional interaction of the representatives of different cultures. The authors conclude that transnational virtual projects give valuable opportunities to develop intercultural communication skills as students learn to make adaptive behavior changes in different cultural contexts, analyse friction points and construct effective strategies for their solution. They gain the ability to synthesize the cultures/languages/rhetorics/spaces in conflict for a constructive communicative outcome.